2020
DOI: 10.3390/ijerph17103397
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of Children’s Exposure to Tobacco Smoke and Parental Smoking Behaviour

Abstract: Around 40% of children are exposed to tobacco smoke, increasing their risk of poor health. Previous research has demonstrated misunderstanding among smoking parents regarding children’s exposure. The parental perceptions of exposure (PPE) measure uses visual and textual vignettes to assess awareness of exposure to smoke. The study aimed to determine whether PPE is related to biochemical and reported measures of exposure in children with smoking parents. Families with at least one smoking parent and a child ≤ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Statistically significant factors were as follows: the number of smokers in the house, perception about the harm of SHS likely to ban smoking in the home than those who did not agree. This result is similar to a study that reported parents who have a high perception of parental risk concerning SHS exposure tended to refrain from smoking in the home (Myers et al, 2020).…”
Section: Resultssupporting
confidence: 89%
“…Statistically significant factors were as follows: the number of smokers in the house, perception about the harm of SHS likely to ban smoking in the home than those who did not agree. This result is similar to a study that reported parents who have a high perception of parental risk concerning SHS exposure tended to refrain from smoking in the home (Myers et al, 2020).…”
Section: Resultssupporting
confidence: 89%
“…Negative parental risk perception also seen in parents allowed household smoking with open window. Similar study showed that parents who allowed household smoking and parents themselves smoking inside the house were found associated with lower parental perception exposure of SHS in children than those smoke strictly outside the house (9). Research showed that up to 52% of the smoker parents reported not believing or not aware about SHS-related adverse health effects in children (23).…”
Section: Discussionmentioning
confidence: 75%
“…Parents who with higher risk perception of SHS exposure to children's health are those who being more protective and practicing smoked away from home. Russian parents showing lower risk perceptions less than parents of other origins (9). In Malaysia, adolescent who were Malays and descendants of natives of Sabah and Sarawak were more likely to expose to SHS than those with the Chinese and Indian parents (10).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations